Pollen and nectar have different effects on the development and reproduction of noctuid moths - He, Limei; Zhao, Shengyuan; He, Wei; Wu, Kongming (Frontiers in Ecology and Evolution, 2022)
Although many noctuid insects are agricultural pests that threaten food production, they are also the major nocturnal pollinators of flowering plants. Larval foods of noctuid pest insects have been well studied for developing control strategies, but knowledge on host plants for the adults is rather scarce. Here, the impact of plant-derived foods on adult survival, fecundity and reproductive physiology of four global species of noctuid pests (Mythimna separata Walker, Mythimna loreyi Duponchel, Athetis lepigone Möschler and Hadula trifolii Hufnagel) was assessed in laboratory experiments. Our results indicated that nectar slowed testis decay and prolonged the oviposition period and lifespan, increasing fecundity. Acacia nectar increased the longevity of male and female adults by 3.2 10.9 and 2.4 5.0 days, respectively, and fecundity of females by 1.22 3.34 times compared to water-fed individuals. The fitness among the different species of noctuid moths differed on specific pollen diets. On pine pollen, the fecundity of female moths of M. separata, A. lepigone and H. trifolii was 10.06%, 33.52%, and 28.61%, respectively, lower than those of the water-fed females, but the fecundity of female moths of M. loreyi on pine pollen was 2.11 times greater than for the water-fed individuals. This work provides valuable information on the nutritional ecology for noctuid moths, which can aid the development and design of nutritional attractants within noctuid pests-infected cropping systems and provide a basis for effective and targeted management of global noctuid pests.